2018
DOI: 10.3390/ijerph15081767
|View full text |Cite
|
Sign up to set email alerts
|

Ethiopian Orthodox Fasting and Lactating Mothers: Longitudinal Study on Dietary Pattern and Nutritional Status in Rural Tigray, Ethiopia

Abstract: About half of Ethiopians belong to the Orthodox Tewahedo religion. Annually, more than 200 days are dedicated to religious fasting, which includes abstaining from all types of food, animal source foods, and water. However, the association of fasting with undernutrition remains unknown in Ethiopia. Therefore, dietary pattern and nutritional status of lactating women during lent fasting and non-fasting periods were studied, and predictor variables for maternal underweight were identified. To achieve this, lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 56 publications
4
61
3
Order By: Relevance
“…Based on the anthropometric measurement of body mass index, 8.2% (95% CI: 7.0-10.0), of lactating women were underweight with BMI less than 18.5 kg/m 2 which prevalence is below the standard acceptable malnutrition rate of 10% (23) .Of the 8.2%, 3.6% were severely underweight, 20.5% were moderately underweight and 75.9% mildly underweight. This prevalence is lower than studies conducted among lactating women in Ethiopia (5,8,12), rural Vietnam (24) and India (25) but higher than a study done in Nigeria (9). The difference in the prevalence of underweight between the current study and the other studies above could be attributed to the differences in the sociodemographic and economic characteristics between these study areas.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Based on the anthropometric measurement of body mass index, 8.2% (95% CI: 7.0-10.0), of lactating women were underweight with BMI less than 18.5 kg/m 2 which prevalence is below the standard acceptable malnutrition rate of 10% (23) .Of the 8.2%, 3.6% were severely underweight, 20.5% were moderately underweight and 75.9% mildly underweight. This prevalence is lower than studies conducted among lactating women in Ethiopia (5,8,12), rural Vietnam (24) and India (25) but higher than a study done in Nigeria (9). The difference in the prevalence of underweight between the current study and the other studies above could be attributed to the differences in the sociodemographic and economic characteristics between these study areas.…”
Section: Discussioncontrasting
confidence: 79%
“…3 LMM is a former global health masters' student at Uppsala University, Sweden 4 MM is the Head of Department of Obstetrics and Gynaecology, Mbale Regional Referral Hospital and a PhD student at Makerere University College of Health Sciences, Uganda. 5 MK is a master's student at the department of Obstetrics and Gynaecology, Makerere University College of Health Sciences, Uganda 6 IAK is a working at the school of public health, Makerere University College of Health Sciences, Uganda 7 RT is a research assistant in the department of Psychiatry, Michigan State University, USA 8 TH is currently pursuing his PhD at the Centre for International Health, University of Bergen, Norway. 9 JK is currently nishing his master's degree at Global Health School of Public Health, Southeast University, Nanjing, 210009, Jiangsu Province, China.…”
Section: Consent For Publicationmentioning
confidence: 99%
“…Avoidance of ASFs during fasting seasons and prioritizing best foods for fathers was reported by most of the study participants. The fasting period of the Ethiopian Orthodox Church accounts for more than 150 days per year and no ASF is consumed by most adults practicing Orthodox Christianity [28,47,48,52]. During this period, ASF may not be prepared at home and be available for children because the mother/caregivers are not willing to prepare non-fasting foods for their children during the fasting season due to their fear that it could contaminate utensils used for cooking family foods [28,46,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that growth was improved among children consuming two food groups or more compared with 0–1 food groups. The benefits from improved dietary diversity even at the very low levels may be partly explained by widespread challenges in Ethiopia with delayed initiation of complementary feeding, as observed in this study and in national statistics (51% of children 6–8 months do not yet consume complementary foods; Central Statistical Agency, ), and by high prevalence of religious fasting that prohibits adherents from eating animal source foods for more than 200 days per year (Desalegn, Lambert, Riedel, Negese, & Biesalski, ). Diversity of the diet also increased with child age in months, indicating that children of complementary feeding age were slow to begin consuming a wider range of food groups.…”
Section: Discussionmentioning
confidence: 72%